The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.1186/s42269-024-01174-6
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and inflammation: elucidating mechanisms of smoking-attributable pathology for therapeutic targeting

Tamer A. Addissouky,
Ibrahim El Tantawy El Sayed,
Majeed M. A. Ali
et al.

Abstract: Background Tobacco smoking remains a major preventable cause of disease and death worldwide. Combustible cigarettes release thousands of chemicals that can initiate inflammatory pathways leading to smoking-related illness. This review aims to synthesize current scientific knowledge on mechanisms of smoking-induced disease, epidemiological trends, and clinical strategies from recent literature. Main body of the abstract At the cellular level, cigare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 110 publications
1
0
0
Order By: Relevance
“…Cigarette smoke induces oxidative stress, inflammation, and cellular senescence throughout various organ systems at the fundamental science level. 31 , 32 Furthermore, Pezzuto et al indicate that even one month of short-term smoking cessation improved lung function and cholesterol levels, which corroborates our results of smokers exhibiting worse survival on respiratory or cardiovascular disease. 33 Furthermore, we revealed that nonsmokers with COPD demonstrated a lower risk of all-cause mortality than smokers without COPD.…”
Section: Discussionsupporting
confidence: 90%
“…Cigarette smoke induces oxidative stress, inflammation, and cellular senescence throughout various organ systems at the fundamental science level. 31 , 32 Furthermore, Pezzuto et al indicate that even one month of short-term smoking cessation improved lung function and cholesterol levels, which corroborates our results of smokers exhibiting worse survival on respiratory or cardiovascular disease. 33 Furthermore, we revealed that nonsmokers with COPD demonstrated a lower risk of all-cause mortality than smokers without COPD.…”
Section: Discussionsupporting
confidence: 90%
“…The high rates of morbidity and mortality associated with exposure to tobacco smoke are due to the cytotoxic, mutagenic, genotoxic, and carcinogenic effects of cigarette smoke constituents and combustion products ( Sołtysiak et al, 2024 ). Tobacco releases a complex mixture of more than 7,000 chemical constituents characterized by a gaseous mixture of irritating and toxic gases (carbon monoxide, volatile organic compounds, SO, NO) and a solid residue, consisting of fine dust and fine and ultrafine particles ( Di Giacomo et al, 2018 ), including carcinogens, oxidants, and toxins that can initiate inflammatory pathways that lead to smoking-related diseases ( Addissouky et al, 2024 ).…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning approaches including transformer models also exhibit promise for dissecting complex datasets to determine HCC prognosis after locoregional treatments such as radiofrequency ablation (RFA). [6][7][8][9][10] By harnessing diverse data sources, robust predictive systems can be developed to direct treatment decisions and follow-up care. In addition to prediction, elucidating disease mechanisms is fundamental for identifying therapeutic targets and improving models.…”
Section: Introductionmentioning
confidence: 99%